Trifluoromethylated Amidrazone Derivatives as Key Compounds for the Synthesis of 4-Aryl-3,5-bis(trifluoromethyl)-4H-1,2,4-triazoles - Zeinali, Najmeh; Darehkordi, Ali (Synthesis, 2022)
A novel, efficient, and solvent-free approach for the synthesis of aryl-3,5-bis(trifluoromethyl)-4H-1,2,4-triazoles is disclosed via the nucleophilic intramolecular cyclization reaction of trifluoromethylated amidrazone and 2,2,2-trifluoroacetic anhydride. The trifluoromethylated amidrazone intermediates used in this project are synthesized from the reaction of N-aryl-2,2,2-trifluoroacetimidoyl chloride derivatives and hydrazine hydrate at ambient temperature in excellent yields.
Keywords: aryl-3,5-bis(trifluoromethyl)-4H-1,2,4-triazole; hydrazine hydrate; trifluoromethylated amidrazones; trifluoroacetimidoyl chlorides; trifluoroacetimidohydrazides; 1,2,4-triazoles; N-heterocycles